2016
DOI: 10.3389/fpsyg.2016.01735
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Averaging in Individuals with Autism Spectrum Disorder

Abstract: There is mounting evidence that observers rely on statistical summaries of visual information to maintain stable and coherent perception. Sensitivity to the mean (or other prototypical value) of a visual feature (e.g., mean size) appears to be a pervasive process in human visual perception. Previous studies in individuals diagnosed with Autism Spectrum Disorder (ASD) have uncovered characteristic patterns of visual processing that suggest they may rely more on enhanced local representations of individual objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 75 publications
2
12
0
Order By: Relevance
“…The presence of a time‐order effect in the ASD group demonstrates that adults with ASD can implicitly infer the mean of the stimuli, and have their perception biased by this prior knowledge. This result is consistent with other studies involving children or adults with ASD and showing that their perception is indeed influenced by prior knowledge [Corbett et al, 2016; Croydon et al, 2017; Manning, Tibber, Charman, Dakin, & Pellicano, 2015; Sapey‐Triomphe, 2017; Van de Cruys et al, 2017]. As priors were found to modulate the perceptual experience of adults with ASD, it does not support the theory suggesting that ASD is characterized by uniformly weak priors [Pellicano & Burr, 2012].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The presence of a time‐order effect in the ASD group demonstrates that adults with ASD can implicitly infer the mean of the stimuli, and have their perception biased by this prior knowledge. This result is consistent with other studies involving children or adults with ASD and showing that their perception is indeed influenced by prior knowledge [Corbett et al, 2016; Croydon et al, 2017; Manning, Tibber, Charman, Dakin, & Pellicano, 2015; Sapey‐Triomphe, 2017; Van de Cruys et al, 2017]. As priors were found to modulate the perceptual experience of adults with ASD, it does not support the theory suggesting that ASD is characterized by uniformly weak priors [Pellicano & Burr, 2012].…”
Section: Discussionsupporting
confidence: 93%
“…These Bayesian theories of ASD were formulated based on post‐hoc interpretations of studies, but more recently, some empirical studies were designed to directly assess prior influence on perception in ASD. Behavioral studies showed that individuals with ASD were able to make perceptual averaging and were influenced by prior knowledge, suggesting intact priors in ASD [Corbett, Venuti, & Melcher, 2016; Croydon, Karaminis, Neil, Burr, & Pellicano, 2017; Ego et al, 2016; Van de Cruys, Vanmarcke, Van de Put, & Wagemans, 2017]. In contrast, some studies concluded on a decreased use of prior knowledge in children and young adults with ASD [Karaminis et al, 2016; Król & Król, 2019].…”
Section: Introductionmentioning
confidence: 99%
“…It should also be noted that our results here pertain directly to ensemble processing of the size of objects in an array, and these results may not generalize to ensemble processing of all types of stimulus features. Though these results are similar to previous findings of decreased ensemble processing of size, color, and facial identity (Corbett et al 2016;Maul et al, 2016;Rhodes et al, 2014;Van der Hallen et al, 2017), this decrease was not observed with ensemble processing of emotional expression (Karaminis et al, 2017) or with more homogeneous arrays (Van der Hallen et al, 2017). As such, future research incorporating multiple measures of ensemble processing across an array of stimulus features would be quite beneficial.…”
Section: Discussionsupporting
confidence: 90%
“…Individuals with ASD are able to represent some level of ensemble information, but this representation may be compromised when compared to TD individuals (Corbett, Venuti, & Melcher, 2016;Maul, Stanworth, Pellicano, & Franklin, 2016;Rhodes, Neumann, Ewing, & Palermo, 2014), though experimental variables such as ensemble heterogeneity may influence this effect (Van der Hallen et al, 2017). The results of the present study expand these latter findings to suggest that these findings are not constrained to individuals with a clinical diagnosis, but can also be observed in the general population relative to their individual level of autistic traits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation